Effect of initial alpha-phase content on microstructure and mechanical properties of sintered silicon carbide - Kim, YW; Mitomo, M; Emoto, H; Lee, JG (AMER CERAMIC SOC, 1998)
By using alpha- and beta-SiC starting powders with similar particle sizes, the effects of initial cu-phase content on the microstructure and the mechanical properties of the liquid-phase-sintered and subsequently annealed materials were investigated. The microstructures developed were analyzed by image analysis. When beta-SiC powder was used, the grains became elongated. The average diameter decreased with increasing alpha-SiC content and the aspect ratio showed a maximum at 10% alpha-SiC and decreased with increasing alpha-SiC content in the starting powder. Such results suggest that microstructure can be controlled by changing alpha-phase content in starting powders. The strength increased with increasing alpha-SiC content in the starting powder while the fracture toughness decreased with increasing alpha-SiC content. There may be a trade-off in improving both the strength and toughness in SiC ceramics sintered with oxide additives.
Keywords: R-CURVE BEHAVIOR; FRACTURE-TOUGHNESS; BETA->ALPHA TRANSFORMATION; AL2O3 ADDITIONS; CERAMICS; NITRIDE